A new methodology for estimation of initial entrainment fraction in annular flow for improved dryout prediction. (January 2015) - Dasgupta, A.; Chandraker, D.K.; Vishnoi, A.K.; Vijayan, P.K.
Highlights: Importance of a closure for initial entrainment fraction (IEF) is highlighted. A new methodology has been presented to predict IEF in diabatic annular flow. The predicted IEF is seen to predict dryout better than ad-hoc IEF values. Abstract: The estimation of dryout power holds a lot of importance in safety of boiling water reactors (BWRs). The basic mechanism of dryout is the depletion of the liquid film adhering to the walls under the combined action of deposition, entrainment and vaporization. In literature, the rate processes of entrainment and deposition have been correlated empirically and woven into a model for dryout prediction. The greatest advantage of this model is that the formulation for tubular geometry can be extrapolated to rod-bundles, with certain modifications and modeling assumptions. An accurate model thus, has the potential to make redundant the numerous dryout correlations which exist for various rod-bundle geometries. This is the reason why this model has gained a lot of popularity. Initial entrainment fraction (IEF), i.e., the fraction of liquid entrained as droplets at the onset of annular flow is an important boundary condition required for the model. However there is very little theoretical or experimental work towards prediction of IEF. In this paper, a new methodology is presented whereby the IEF can be determined. It is seen that predictions are improved upon using the new method.